2022
DOI: 10.1007/s00431-021-04350-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID-19 pandemic on hospitalizations and disease characteristics of adolescents with anorexia nervosa

Abstract: Social distancing and quarantines have major negative psychological implications. Our aim was to study the rate of pediatric hospitalizations due to anorexia nervosa (AN) during the first year of coronavirus disease 2019 (COVID-19) pandemic as compared to previous years, with regard to clinical and laboratory parameters. This is a retrospective study in a tertiary pediatric hospital in Israel. Data regarding inpatient hospitalizations due to AN were retrieved, then epidemiological, clinical, and laboratory par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 11 publications
7
26
2
Order By: Relevance
“…This raises the question of whether it was only the most severe cases that came to the hospital. In our study, in line with the results reported by Goldberg et al [ 17 ], this increase in hospitalizations for AN did not seem to be associated with increased medical severity (i.e., ICU admission and lethality). Moreover, bearing in mind the overall decreases in psychological health, we found that admissions for self-harm in young patients with AN increased in the post-lockdown period, with a peak in the winter of 2020–2021.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This raises the question of whether it was only the most severe cases that came to the hospital. In our study, in line with the results reported by Goldberg et al [ 17 ], this increase in hospitalizations for AN did not seem to be associated with increased medical severity (i.e., ICU admission and lethality). Moreover, bearing in mind the overall decreases in psychological health, we found that admissions for self-harm in young patients with AN increased in the post-lockdown period, with a peak in the winter of 2020–2021.…”
Section: Discussionsupporting
confidence: 93%
“…However, there are conflicting data with respect to the impact of the pandemic on eating disorders. Several reports showed clinical improvements and reductions in hospitalizations after lockdown for patients with AN [ 16 , 17 ], whereas other research suggests deleterious effects on young patients with AN [ 18 , 19 , 20 ]. It thus seemed relevant to further investigate the influence of the COVID-19 pandemic on people with AN [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Haripersad et al [ 5 ] and Hansen et al [ 6 ] reported a large increase in hospital admissions because of AN in adolescents during the COVID-19 pandemic in Western Australia and in a mixed urban–rural area in New Zealand, respectively. Similar trends for adolescents with AN were observed in Canada, with higher admission rates in regions with higher infection rates [ 7 ], and an Israelian study reported a 2.4-fold increase in admission rates of adolescents to the largest Israeli paediatric tertiary care hospital during the COVID-19 pandemic compared with the period 2015–2019 [ 8 ]. A study from the US demonstrated a large increase in admissions of 10- to 23-year-old patients with eating disorders (ED) during the first 12 months of the pandemic, which was more than double the mean number of admissions per year for the same timeframe for the previous 3 years [ 9 ].…”
Section: Introductionmentioning
confidence: 52%
“…This period is parallel with our study period. During the pandemic there was an increase in hospital mental health related admissions among children and adolescents [16,17]. The information on triggers for PFAPA attacks is scarce.…”
Section: Discussionmentioning
confidence: 99%